Secular Changes in Youth Labour Markets and Youth Unemployment in Canada - Weiermair, Klaus (Relations Industrielles / Industrial Relations, 1986)
This paper considers the evolution of Canadian youth unemployment and associated patterns of behavior in youth labor markets from a long run perspective.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Economic trends; Employment; LABOR market; Labor Unions; Statistical data; Unemployment; Wages & salaries; Younger workers; Youth